Progress and potential of exosome analysis for early pancreatic cancer detection - Erb, Ulrike; Zöller, Margot (Expert review of molecular diagnostics, 2016)
Introduction: Pancreatic cancer (PaCa) is the most deadly malignancy, due to late diagnosis prohibiting surgery. Thus, strong efforts are taken improving early diagnosis via biomarkers recovered in the serum of PaCa patients.Areas covered: One promising option are PaCa-derived exosomes in patients’ sera. Exosomes, small vesicles delivered by live cells and recovered in all body fluids, are a powerful diagnostic tool due to relative stability and composition covering the whole range of cancer-related biomarkers including proteins, metabolites, DNA, DNA modifications, coding and noncoding RNA. We discuss the mechanisms accounting for the condensed packaging of biomarkers, refer to studies using PaCa serum-exosomes for diagnosis. Based on an extensive literature search, we outline questions that answers may help establishing a serum-exosome-based screening for early PaCa detection.Expert commentary: Improved proteomic and genomic characterization and progress in the biogenesis of exosomes will allow for optimized and unified screening panels for PaCa diagnosis via TEX in body fluids.
Gesehen am 08.05.2020